Evaluation of Interleukin – 12 and Interleukin – 23 expressions in patients with active and latent tuberculosis infection (Journal of Pharmaceutical Negative Results, 2022)
Tuberculosis (TB) diagnosis should be performed as early as possible and with accuracy in order to limit the global TB outbreak. Immunological tests that can differentiate between active TB (ATB) and latent TB infection (LTBI) have been identified. To better understand the immunological responses to tuberculosis infection, we conducted two retrospective cohort studies. Participants were divided into three groups: those with ATB, those with LTBI, and those who were not categorized. Our findings from our multiplex cytokine experiment led to the development of a Biomarkers for two distinct cytokines that allows for the most accurate diagnosis of the various TB infection states in humans. It was revealed that TB-antigen induced IFN- was associated with two cytokine biomarkers (n=70) through our investigation. The diagnostic performance of the biosignature was demonstrated higher median levels of IL-12 and IL-23 recorded by the TB group (884.44 pg/ml) and (2750 pg/ml), respectively, in the TB group. Afterwards, it was tested on a biomarker validation cohort, and the results showed that it had 97.1 percent sensitivity as well as 91.4 percent specificity. We have discovered a two-cytokine biosignature that can be used to accurately distinguish ATB patients from people with LTBI and CON, respectively. This procedure has the potential to be used as an early and rapid diagnostic test for ATB.